DEVELOPMENT OF A DIGITAL SURVEILLANCE SYSTEM FOR EARLY DETECTION OF LEPTOSPIROSIS IN BALI: Pengembangan Sistem Surveilans Digital Untuk Deteksi Dini Leptospirosis di Bali - Ayu Ari Shinta Dewi, I Dewa Agung; Subrata, I Made; Putri Agustini, Putu; Surya Pratama, I Gusti Ngurah Agung; Anom Harjana, Ngakan Putu; Gede Purnama, Sang; Muhammad Dary Mufa, Romy (Universitas Airlangga, 2026)
Background: According to the Early Warning Alert and Response System (EWARS) report, five suspected cases of leptospirosis have been reported in Bali Province, including one in Tabanan Regency and four in Denpasar City. However, surveillance activities are still conducted manually using paper-based methods, which leads to issues such as incomplete reports, duplicate data entry, and limited data access. Purpose: This study aims to design a digital epidemiological surveillance system integrated with rat sentinel surveillance as an early detection tool for leptospirosis in Bali Province. Methods: The study employed a Research and Development (R&D) design, with prototype development using the System Development Life Cycle (SDLC) model. Data were collected through interviews and questionnaires with 33 surveillance officers from health departments in Denpasar and Tabanan, selected purposively. Data collection took place from August 2023 to March 2024. Results: The surveillance officers responded positively to the system design. The perceived usefulness, ease of use, ease of learning, and user satisfaction were 82%, 81%, 83%, and 83%, respectively. The overall usability score reached 82%, categorized as “highly feasible.” Conclusion: The leptospirosis surveillance system design was well received by surveillance officers and has strong potential to be implemented as an early detection tool in Bali.